Intranasal Dopamine Reduces In Vivo [123I]FP-CIT Binding to Striatal Dopamine Transporter: Correlation with Behavioral Changes and Evidence for Pavlovian Conditioned Dopamine Response - de Souza Silva, Maria A.; Mattern, Claudia; Decheva, Cvetana; Huston, Joseph P.; Sadile, Adolfo G.; Beu, Markus; Müller, H.-W.; Nikolaus, Susanne (Frontiers in Behavioral Neuroscience, 2016)
Purpose: Dopamine (DA), which does not cross the blood-brain barrier, has central and behavioral effects when administered via the nasal route. Neither the mechanisms of central action of intranasal dopamine (IN-DA), nor its mechanisms of diffusion and transport into the brain are well understood. We here examined whether IN-DA application influences dopamine transporter (DAT) binding in the dorsal striatum and assessed the extent of binding in relation to motor and exploratory behaviors. We hypothesized that, based on the finding of increased extracellular DA in the striatum induced by application of IN-DA, binding of [123I]FP-CIT to the DAT should be decreased due to competition at the receptor. Methods: Rats were administered 3 mg/kg IN-DA and vehicle (VEH), with IN-DA injection either preceding or following VEH. Then motor and exploratory behaviors (traveled distance, velocity, center time, sitting, rearing, head-shoulder motility, grooming) were assessed for 30 min in an open field prior to administration of [123I]FP-CIT. DAT binding after IN-DA and VEH was measured with small animal SPECT 2 h following administration of the radioligand. Results: (1) After IN-DA application, striatal DAT binding was significantly lower as compared to VEH, indicating that the nasally delivered DA had central action and increased DA levels comparable to that found previously with L-DOPA administration; and (2) DAT binding in response to intranasal VEH was lower when IN-DA application preceded VEH treatment. This finding is suggestive of Pavlovian conditioning of DA at the level of the DAT, since the DA treatment modified (decreased) the binding in response to the subsequent VEH treatment. VEH treatment also reduced motor and exploratory behaviors more when applied before, as compared to when it followed IN-DA application, also indicative of behavioral Pavlovian conditioning akin to that found upon application of various psychostimulant drugs. Conclusions: The results: (a) demonstrate a direct central action of intranasally applied DA on the DAT in the dorsal striatum, indicating enhanced DA availability; and (b) provide first evidence of a Pavlovian conditioned DA response at the DAT. The latter results have relevance to understanding neurochemical mechanisms that underlie placebo action in the treatment of Parkinsonian patients.